High-flame-retardant and environment-friendly urea-formaldehyde resin adhesive as well as preparation process and application thereof

By using modified aluminum tripolyphosphate formaldehyde capture agent and three-stage polymerization process in particle board, a high flame retardant and environmentally friendly urea formaldehyde resin adhesive was prepared, which solved the problems of formaldehyde release and flammability in particle board, and achieved significant Reduced formaldehyde and improved flame retardant performance.

CN119391326AActive Publication Date: 2025-02-07GUANGXI KECUBIC NEW MATERIAL CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411716322.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-07
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The free formaldehyde content in existing particleboards is high and flammable, which limits its downstream application and development.

Method used

Modified aluminum tripolyphosphate formaldehyde capture agent and three-stage polymerization process are used to prepare high flame retardant, environmentally friendly urea-formaldehyde resin adhesive. By finely controlling the amount of raw materials and process parameters, the formaldehyde emission is reduced and the flame retardant performance is improved.

Benefits of technology

It significantly reduces the formaldehyde emission of particleboard, reaches the E0 standard, and improves its flame retardant performance, reaches the flame retardant grade B1-C, improving indoor air quality and overall safety of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391326A_ABST
    Figure CN119391326A_ABST
Patent Text Reader

Abstract

The preparation process comprises the following steps: adding a formaldehyde solution into a reaction kettle, adjusting the pH value of the formaldehyde solution by using sodium hydroxide, adding urea for the first time, starting a stirrer, carrying out a heating reaction, increasing the reaction temperature, adding urea for the second time, carrying out a stirring reaction, increasing the temperature, and carrying out cooling, so as to obtain the high-flame-retardant environment-friendly urea-formaldehyde resin adhesive. After the reaction is finished, adding the modified aluminum triphosphate formaldehyde trapping agent into the reaction kettle, uniformly stirring, cooling to room temperature, and discharging, so as to obtain the high-flame-retardant and environment-friendly urea-formaldehyde resin adhesive. The preparation process is simple, the obtained urea-formaldehyde resin adhesive is low in price, basic adhesion requirements of shaving boards can be met, release of formaldehyde of the shaving boards can be reduced, flame retardance of the shaving boards can be improved, and environmental protection and safety of the shaving boards are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial board production, in particular to a preparation process of a urea-formaldehyde resin adhesive which has low free formaldehyde content and can impart higher flame retardancy to particleboard. Background Art

[0002] Particleboard using urea-formaldehyde resin as a binder has become one of the main types of particleboard at home and abroad due to its advantages such as low cost, easy availability of raw materials and simple process. However, due to the high content of free formaldehyde in the urea-formaldehyde resin glue used and the flammable characteristics of particleboard itself, the downstream application and development of particleboard are greatly restricted.

[0003] Patent CN116175715A discloses a composite inorganic flame retardant for particleboard. The composite inorganic flame retardant uses spherical calcium silicate crystals with a multilayer flaky structure and a large specific surface area as a carrier to adsorb and carry inorganic flame retardants, and then adheres to the surface of the shavings with the help of a cross-linking agent to improve its anti-loss property and ensure its flame retardant life after application. The calcium silicate crystals are macroscopically powdery and can be filled in the gaps of the shavings when used, and can also improve the density of the particleboard to a certain extent. The invention also discloses a flame-retardant particleboard using the above composite inorganic flame retardant and a method for making the same. The flame-retardant particleboard uses the above anti-loss composite inorganic flame retardant as the main flame retardant component. While exerting a flame retardant effect, it also effectively achieves the purpose of anti-loss and extends the flame retardant life of the board. Its production method is no different from the existing production method of general flame-retardant particleboards, and the process is simple. This invention is mainly intended to solve the problems of flammability and leakage of particleboard, but fails to effectively utilize the adsorption properties of the multi-layered sheet structure of calcium silicate to solve the problem of formaldehyde release from particleboard.

[0004] Patent CN115838576A discloses a formaldehyde-free adhesive and its application in the preparation of P2P12 grade particleboard, belonging to the technical field of plywood. It includes an emulsion, a crosslinking agent and an inorganic filler, wherein the emulsion includes emulsion A and emulsion B, wherein emulsion A is obtained by solution polymerization of vinyl acetate, vinyl chloride and ethylene; and emulsion B is obtained by solution polymerization of a rigid monomer and butadiene, wherein the rigid monomer includes at least one of styrene, p-methylstyrene, o-methylstyrene and m-methylstyrene. Under the synergistic effect of emulsion A and emulsion B, the particleboard can simultaneously have excellent flame retardancy, water resistance and physical and mechanical properties. The invention involves multiple chemical reactions, and the process is relatively complicated, which is difficult to stably control in actual operation. In addition, it also fails to solve the problem of formaldehyde release from particleboard.

[0005] In summary, existing research has failed to simultaneously solve the high formaldehyde content and flammability of particleboard. In view of the above shortcomings of particleboard using urea-formaldehyde resin adhesive, such as high free formaldehyde content and flammability, a new preparation method of urea-formaldehyde resin adhesive is proposed, aiming to simultaneously solve the problems of formaldehyde release and flammability of particleboard. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a urea-formaldehyde resin adhesive to solve the problems of high free formaldehyde content and flammability of particleboard mentioned in the above background technology.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] A method for preparing a modified aluminum tripolyphosphate formaldehyde scavenger comprises the following steps:

[0009] Aluminum tripolyphosphate suspension is added to the reactor, and the temperature of the aluminum tripolyphosphate suspension is increased under stirring. The composite modifier is added to the reactor, and after stirring, the modified aluminum tripolyphosphate formaldehyde capture agent is obtained through filter pressing, drying and crushing.

[0010] Preferably, the dry basis mass of the aluminum tripolyphosphate suspension is 40-45%.

[0011] Preferably, the temperature of the aluminum tripolyphosphate suspension is increased to 65-70°C.

[0012] Preferably, the added amount of the composite modifier is 4.5-5% of the aluminum tripolyphosphate dry basis equivalent.

[0013] Preferably, the preparation method of the composite modifier comprises the following steps: adding deionized water into a container, then heating, adding polyvinyl alcohol under stirring conditions, and after the polyvinyl alcohol is completely dissolved, adding ethylene urea and meta-diphenol at the same time, and after both are completely dissolved, cooling the solution to obtain the composite modifier.

[0014] Preferably, deionized water is added to the container and then heated to 65-70°C.

[0015] Preferably, the mass ratio of the deionized water, polyvinyl alcohol, ethylene urea and m-diphenol is (45-50):(10-15):(20-25):(30-35).

[0016] The present invention also provides a preparation process of a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive, comprising the following steps:

[0017] A formaldehyde solution with a content of 35-37% is added to a reaction kettle, and the pH value of the formaldehyde solution is adjusted to between 7.5 and 8.0 using 28-30% sodium hydroxide. Urea is added for the first time in an amount of 80-82% of the total mass of urea, and the stirrer is started, heated to 70-75°C for reaction for 1-2 hours, and the reaction temperature is increased to 80-85°C. Urea is added for the second time in an amount of 13-15% of the total mass of urea, and the reaction is stirred for 1-1.5 hours, and the temperature is increased to 90-95°C. Urea is added for the third time in an amount of 4-6% of the total amount of urea, and the reaction is terminated after 1-1.5 hours. The total mass of the added urea is 1.7-1.8 times the amount of formaldehyde. The modified aluminum tripolyphosphate formaldehyde capture agent described in any one of claims 1 to 7 is added to the reaction kettle, and after being stirred evenly, the material is cooled to room temperature and discharged to obtain a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive.

[0018] The present invention also provides an application of a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive, which is applied in the production of artificial boards.

[0019] Compared with the prior art, the present invention has significant technical advantages, which are specifically reflected in the following aspects:

[0020] 1. High efficiency and cost-effectiveness of the preparation process: The preparation process of the present invention is designed to be extremely concise and clear, which is not only convenient to operate, but also greatly reduces the complexity and energy consumption in the production process. Through this optimized process, the present invention successfully prepares a low-cost urea-formaldehyde resin adhesive. This adhesive can not only fully meet the basic requirements of particleboard in terms of adhesion strength, ensure the structural stability and durability of the product, but also achieve a qualitative leap in environmental protection and safety performance. Specifically, it significantly reduces the amount of formaldehyde released by particleboard during use, which is of great significance for improving indoor air quality and protecting user health. At the same time, the adhesive of the present invention also significantly improves the flame retardant properties of particleboard, so that it can more effectively resist the spread of fire when facing emergencies such as fire, thereby greatly improving the overall safety of the product. This series of improvements undoubtedly makes the urea-formaldehyde resin adhesive of the present invention more competitive in the market.

[0021] 2. The singleness of chemical reaction and the stability of product performance: The reason why the preparation process of the present invention can achieve high efficiency and low cost is that the key is that the preparation process of the entire adhesive resin involves only one chemical reaction. This single reaction path not only simplifies the production process, but also helps to obtain an adhesive resin with stable performance. The carefully designed preparation process of the present invention is divided into three stages for condensation reaction, and each stage is precisely controlled and optimized to ensure that the reaction can be carried out more thoroughly. This staged reaction method not only improves the conversion rate of formaldehyde, reduces the residual amount of formaldehyde, thereby reducing pollution to the environment, but also further reduces the production cost, making the adhesive of the present invention more advantageous in price. In addition, the present invention also specifically adds a modified aluminum tripolyphosphate formaldehyde scavenger. This scavenger can not only efficiently absorb the remaining formaldehyde in the resin and further reduce the formaldehyde content, but also has good flame retardant properties, providing additional safety for particleboard. The combination of this multiple advantages has enabled the urea-formaldehyde resin adhesive of the present invention to achieve significant technical progress and brought new development opportunities to related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the modified aluminum tripolyphosphate formaldehyde scavenger obtained in Example 1. DETAILED DESCRIPTION

[0023] The present invention will be described in detail below in conjunction with specific embodiments and drawings of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0024] In an embodiment of the present invention:

[0025] The preparation method of the composite modifier comprises the following steps: adding 45 to 50 parts of deionized water into a container, heating to 65 to 70° C., adding 10 to 15 parts of polyvinyl alcohol under stirring conditions, and after the polyvinyl alcohol is completely dissolved, adding 20 to 25 parts of cycloethylene urea and 30 to 35 parts of meta-diphenol at the same time, and after the two are completely dissolved, cooling the solution to obtain the composite modifier.

[0026] The preparation method of the modified aluminum tripolyphosphate formaldehyde scavenger comprises the following steps:

[0027] Aluminum tripolyphosphate suspension with a dry basis weight of 40-45% is added to a high-speed stirring reactor. Under stirring, the temperature of the aluminum tripolyphosphate suspension is increased to 65-70° C. A composite modifier with a dry basis weight of 4.5-5% of aluminum tripolyphosphate is added to the reactor. After stirring for 25-30 minutes, the modified aluminum tripolyphosphate formaldehyde capture agent is obtained by filter pressing, drying and crushing.

[0028] The preparation method of a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive comprises the following steps:

[0029] Add an appropriate amount of formaldehyde solution with a content of 35-37% to the reactor, use 28-30% sodium hydroxide to adjust the pH value of the formaldehyde solution to between 7.5 and 8.0, add urea for the first time, the amount of which is 80-82% of the total mass of urea, start the stirrer, heat to 70-75°C for reaction for 1-2 hours, increase the reaction temperature to 80-85°C, add urea for the second time, the amount of which is 13-15% of the total mass of urea, stir for reaction for 1-1.5 hours, raise the temperature to 90-95°C, add urea for the third time, add 4-6% of the total amount of urea, react for 1-1.5 hours, end the reaction, and the total mass of urea added is 1.7-1.8 times the amount of formaldehyde. Add modified aluminum tripolyphosphate formaldehyde capture agent to the reactor, stir evenly, cool to room temperature and discharge, and obtain a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive.

[0030] Technical principle of the present invention:

[0031] In the field of chemical synthesis, precise control of raw material dosage and optimization of process parameters are the key to ensuring product quality, improving production efficiency and achieving specific performance. The following is an in-depth analysis of the preparation method of the composite modifier, modified aluminum tripolyphosphate formaldehyde scavenger and urea-formaldehyde resin adhesive in the present invention, focusing on the necessity and importance of controlling raw material dosage and optimizing process parameters.

[0032] 1. Preparation method of composite modifier

[0033] 1. The necessity of raw material dosage control:

[0034] Deionized water (45-50 parts): As a solvent, its dosage directly affects the solubility of subsequent solutes and the concentration of the solution, and further affects the physical properties of the modifier, such as viscosity and fluidity. An appropriate amount of deionized water can ensure that the solute is fully dissolved and avoid agglomeration caused by excessive local concentration.

[0035] Polyvinyl alcohol (10-15 parts): As one of the main components of the modifier, its dosage determines the basic skeleton structure and performance of the modifier. An appropriate amount of polyvinyl alcohol can enhance the adhesion and water resistance of the modifier.

[0036] Ethylene urea (20-25 parts), meta-diphenol (30-35 parts): These two additives work together to optimize the performance of the modifier, such as improving heat resistance, chemical corrosion resistance, etc. Their dosage needs to be precisely controlled to ensure that the overall performance of the modifier is optimal.

[0037] 2. The process steps cannot be changed or optimized:

[0038] First, polyvinyl alcohol is added and waited for its complete dissolution, and then ethylene urea and m-diphenol are added. This order ensures that the solutes are gradually dissolved and avoids uneven mixing due to differences in solubility.

[0039] The solution cooling process is also key, as it helps stabilize the structure of the modifier and prevents performance degradation due to high temperature.

[0040] 2. Preparation method of modified aluminum tripolyphosphate formaldehyde scavenger

[0041] 1. The necessity of raw material dosage control:

[0042] Aluminum tripolyphosphate suspension (dry basis weight 40-45%): As the main material, its content directly affects the formaldehyde adsorption capacity and stability of the capture agent. An appropriate amount of aluminum tripolyphosphate can ensure that the capture agent has sufficient active sites to effectively capture formaldehyde.

[0043] Composite modifier (4.5-5% of aluminum tripolyphosphate dry basis equivalent): The introduction of composite modifier can significantly improve the dispersibility and weather resistance of the capture agent. Its dosage needs to be precisely controlled to avoid performance degradation caused by excessive or insufficient addition.

[0044] 2. Importance of process parameter optimization:

[0045] Increasing the temperature to 65-70°C helps accelerate the reaction rate and ensure that the composite modifier is evenly dispersed in the aluminum tripolyphosphate suspension.

[0046] Precise control of the stirring time (25-30 min) ensures that the reaction proceeds fully while avoiding increased energy consumption and equipment wear caused by excessive stirring.

[0047] 3. Preparation method of urea-formaldehyde resin adhesive

[0048] 1. The necessity of raw material dosage control:

[0049] Formaldehyde solution (35-37%): As a reaction raw material, its content directly affects the formaldehyde release and curing speed of the adhesive. The right amount of formaldehyde can ensure that the adhesive has a suitable curing time and strength.

[0050] Urea (total amount is 1.7-1.8 times the amount of formaldehyde): add in three times, and adjust the amount each time according to the reaction progress to control the crosslinking degree and viscosity of the adhesive. The right amount of urea can ensure that the adhesive has excellent bonding strength and water resistance.

[0051] 2. Importance of process parameter optimization:

[0052] Adjusting the pH value to 7.5-8.0 helps promote the condensation reaction of urea and formaldehyde, and improves reaction efficiency and product quality.

[0053] The gradual increase in temperature (70-75°C → 80-85°C → 90-95°C) and the staged addition of urea achieve precise control of the reaction process and avoid performance degradation caused by local overheating and excessive cross-linking.

[0054] After adding modified aluminum tripolyphosphate formaldehyde scavenger, not only the formaldehyde capture ability of the adhesive is improved, but also it is endowed with high flame retardant properties, achieving a dual improvement in environmental protection and performance.

[0055] In summary, the present invention successfully prepared high-performance composite modifiers, modified aluminum tripolyphosphate formaldehyde scavengers and urea-formaldehyde resin adhesives by precisely controlling the amount of raw materials and optimizing process parameters. These measures not only ensure the quality and stability of the products, but also achieve unexpected technical effects, such as improving the heat resistance, chemical corrosion resistance and flame retardancy of the products, and meeting the market demand for high-performance, environmentally friendly adhesives.

[0056] Mechanism of reducing formaldehyde: In the process of condensation of urea and formaldehyde, a three-stage condensation is adopted to make the polymerization as sufficient as possible and reduce the total amount of free formaldehyde. By adding the modified aluminum tripolyphosphate formaldehyde capture agent of the present invention, the aluminum tripolyphosphate of the present invention has a multi-layered layered structure and is modified by composite polyvinyl alcohol, ethylene urea, and meta-diphenol. The three substances can react with formaldehyde under different temperatures and reaction conditions (for example, meta-diphenol reacts with formaldehyde under acidic conditions, and polyvinyl alcohol reacts with formaldehyde under alkaline conditions), thereby achieving the effect of eliminating formaldehyde. The reaction conditions between the three and formaldehyde complement each other to achieve the effect of maximum reaction with formaldehyde; the layered structure of aluminum tripolyphosphate has a certain adsorption effect on formaldehyde, and aluminum tripolyphosphate reacts the adsorbed formaldehyde with its surface modifier, such as polyvinyl alcohol and formaldehyde can generate polyvinyl alcohol formal, meta-diphenol reacts with formaldehyde to generate phenolic resin, and solidifies volatile formaldehyde, so as to finally achieve the purpose of completely eradicating formaldehyde.

[0057] Flame retardant mechanism: Aluminum tripolyphosphate can effectively promote the rapid dehydration and carbonization of hydrocarbon substances in particleboard in the early stage of fire, so that the polymer material cannot produce flammable gas and prevent the fire from further intensifying. In addition, aluminum tripolyphosphate will decompose into aluminum metaphosphate at high temperature. Aluminum metaphosphate is a glassy substance with excellent heat resistance. It can wrap flammable materials and act as an isolation layer.

[0058] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.

[0059] Example 1

[0060] 1. Add 40% aluminum tripolyphosphate suspension on a dry basis to a high-speed stirring reactor. Under stirring, raise the temperature of the aluminum tripolyphosphate suspension to 65°C. Add 5% of the aluminum tripolyphosphate dry basis equivalent composite modifier (deionized water / polyvinyl alcohol / ethylene urea / m-diphenol = 47 / 13 / 20 / 35) to the reactor. After stirring for 30 minutes, filter press, dry and crush to obtain a modified aluminum tripolyphosphate formaldehyde scavenger. SEM pictures are shown in Figure 1 .

[0061] 2. Add an appropriate amount of 37% formaldehyde solution to the reactor, use 30% sodium hydroxide to adjust the pH value of the formaldehyde solution to 7.6, add urea for the first time, the amount added is 80% of the total mass of urea, start the stirrer, heat to 70°C for reaction for 1h, raise the reaction temperature to 80°C, add urea for the second time, the amount added is 15% of the total mass of urea, stir and react for 1h, raise the temperature to 90°C, add urea for the third time, add 5% of the total amount of urea, react for 1h, the reaction ends, and the total mass of urea added is 1.8 times the effective content of formaldehyde. Add the modified aluminum tripolyphosphate formaldehyde capture agent prepared in step 1 to the reactor, stir evenly, cool to room temperature and discharge, and obtain the sample of the urea-formaldehyde resin adhesive of Example 1.

[0062] Example 2

[0063] 1. Add 42% aluminum tripolyphosphate suspension on a dry basis to a high-speed stirring reactor, raise the temperature of the aluminum tripolyphosphate suspension to 67° C. under stirring, add 4.5% of a composite modifier (deionized water / polyvinyl alcohol / ethylene urea / m-diphenol=45 / 15 / 22 / 35) on a dry basis equivalent to aluminum tripolyphosphate to the reactor, stir for 25 min, filter press, dry and crush to obtain a modified aluminum tripolyphosphate formaldehyde scavenger.

[0064] 2. Add an appropriate amount of 36% formaldehyde solution to the reactor, use 29% sodium hydroxide to adjust the pH value of the formaldehyde solution to 7.7, add urea for the first time, the amount added is 81% of the total mass of urea, start the agitator, heat to 72°C for reaction for 1.5h, raise the reaction temperature to 82°C, add urea for the second time, the amount added is 14% of the total mass of urea, stir the reaction for 1.5h, raise the temperature to 92°C, add urea for the third time, add 5% of the total amount of urea, react for 1.5h, the reaction ends, and the total mass of urea added is 1.7 times the effective content of formaldehyde. Add the modified aluminum tripolyphosphate formaldehyde capture agent prepared in step 1 to the reactor, stir evenly, cool to room temperature and discharge, and obtain the sample of the urea-formaldehyde resin adhesive of Example 2.

[0065] Example 3

[0066] 1. Add 45% aluminum tripolyphosphate suspension on a dry basis to a high-speed stirring reactor, raise the temperature of the aluminum tripolyphosphate suspension to 70°C while stirring, add 4.8% of the aluminum tripolyphosphate dry basis equivalent composite modifier (deionized water / polyvinyl alcohol / ethylene urea / m-diphenol = 50 / 15 / 25 / 30) to the reactor, stir for 28 minutes, filter press, dry and crush to obtain a modified aluminum tripolyphosphate formaldehyde capture agent.

[0067] 2. Add an appropriate amount of 35% formaldehyde solution to the reactor, use 28% sodium hydroxide to adjust the pH value of the formaldehyde solution to 8.0, add urea for the first time, the amount added is 80% of the total mass of urea, start the agitator, heat to 75°C for 1h, raise the reaction temperature to 80°C, add urea for the second time, the amount added is 14% of the total mass of urea, stir and react for 1.5h, raise the temperature to 95°C, add urea for the third time, add 6% of the total amount of urea, react for 1.5h, and end the reaction. The total mass of urea added is 1.7 times the effective content of formaldehyde. Add the modified aluminum tripolyphosphate formaldehyde capture agent prepared in step 1 to the reactor, stir evenly, and cool to room temperature to discharge, and obtain the sample of the urea-formaldehyde resin adhesive of Example 3.

[0068] Comparative Example 1

[0069] 1. Add 40% aluminum tripolyphosphate suspension on a dry basis into a high-speed stirring reactor, raise the temperature of the aluminum tripolyphosphate suspension to 65° C. under stirring, add 5% composite modifier (deionized water / polyvinyl alcohol / ethylene urea / toluenesulfonamide / m-diphenol=47 / 13 / 20 / 35) on a dry basis equivalent to aluminum tripolyphosphate into the reactor, stir for 30 min, filter press, dry and crush to obtain a modified aluminum tripolyphosphate formaldehyde capture agent.

[0070] 2. Add an appropriate amount of 37% formaldehyde solution to the reactor, adjust the pH value of the formaldehyde solution to 7.6 using 30% sodium hydroxide, raise the temperature to 90°C, add urea at one time, the mass of urea added is 1.8 times the effective content of formaldehyde, react for 3 hours, and terminate the reaction. Add the modified aluminum tripolyphosphate formaldehyde capture agent prepared in step 1 to the reactor, stir evenly, cool to room temperature and discharge, and obtain the sample of urea-formaldehyde resin adhesive of Comparative Example 1.

[0071] Comparative Example 2

[0072] Add an appropriate amount of 37% formaldehyde solution to the reactor, use 30% sodium hydroxide to adjust the pH value of the formaldehyde solution to 7.6, add urea for the first time, the amount added is 80% of the total mass of urea, start the stirrer, heat to 70°C for reaction for 1h, increase the reaction temperature to 80°C, add urea for the second time, the amount added is 15% of the total mass of urea, stir for reaction for 1h, raise the temperature to 90°C, add urea for the third time, add 5% of the total amount of urea, react for 1h, the reaction ends, and the total mass of urea added is 1.8 times the effective content of formaldehyde. Cool to room temperature and discharge, and obtain the sample of urea-formaldehyde resin adhesive of Comparative Example 2.

[0073] Comparative Example 3

[0074] Add an appropriate amount of 37% formaldehyde solution to the reactor, use 30% sodium hydroxide to adjust the pH value of the formaldehyde solution to 7.6, add urea for the first time, the amount added is 80% of the total mass of urea, start the stirrer, heat to 70°C for reaction for 1h, raise the reaction temperature to 80°C, add urea for the second time, the amount added is 15% of the total mass of urea, stir for reaction for 1h, raise the temperature to 90°C, add urea for the third time, add 5% of the total amount of urea, react for 1h, the reaction ends, and the total mass of urea added is 1.8 times the effective content of formaldehyde. Add aluminum tripolyphosphate that is not modified with a composite modifier, stir evenly, cool to room temperature and discharge, and obtain a sample of the urea-formaldehyde resin adhesive of Comparative Example 3.

[0075] Effect evaluation method:

[0076] 1. Determination of free formaldehyde content in adhesives

[0077] Weigh about 2g of urea-formaldehyde resin adhesive accurately and place it in a beaker containing 50ml of methanol. Stir with a glass rod for 2 minutes, then add 3 drops of thymol blue indicator. Use dilute hydrochloric acid to adjust the solution color to yellow-green, add 25ml of 10% hydroxylamine hydrochloride, stir evenly, and titrate with 1mol / L sodium hydroxide standard solution until the solution turns blue-green. The end point is when the color does not change for 1 minute. The blank group is operated in this way without adding any test material.

[0078] Formaldehyde content w = 3c (V1-V0) / m

[0079] Where: c-actual concentration of the sodium hydroxide standard solution used, mol / L;

[0080] V0-volume of sodium hydroxide standard titration solution consumed in blank test, ml;

[0081] V1-volume of sodium hydroxide standard titrant consumed in the test, ml;

[0082] m-sample mass, g.

[0083] 2. Determination of formaldehyde emission from particleboard

[0084] The particleboard samples prepared in the examples and comparative examples were 3 The climate chamber method for detecting formaldehyde emissions is mainly based on GB18580-2017 "Formaldehyde emissions from interior decoration and renovation materials, artificial panels and their products".

[0085] 3. Flame retardant performance test of particleboard

[0086] The particleboard samples prepared using the examples and comparative examples were tested according to GB / T39032-2020 "Flame Retardant Particleboard" THR 600S (Total heat released during the first 600 seconds of ignition from the main burner).

[0087] Test results:

[0088] According to the above test method, the results are shown in Table 1:

[0089] Table 1 Sample test results

[0090]

[0091] (1) From the data listed in detail in Table 1, the present invention can clearly observe the significant advantages of Examples 1 to 3 in terms of free formaldehyde content. These values ​​are significantly lower, indicating that their formaldehyde control effect is extremely outstanding. At the same time, the particleboards prepared by these embodiments also perform well in formaldehyde emission, and all successfully reach the E0 level formaldehyde emission standard. This achievement is undoubtedly remarkable. In-depth exploration of the reasons behind it, the present invention can find that this is mainly due to the clever use of a three-stage polymerization process in the process of synthesizing urea-formaldehyde resin, combined with modified aluminum tripolyphosphate as an additive. The three-stage polymerization process ensures the full reaction of formaldehyde and urea by finely controlling the reaction conditions, thereby effectively reducing the generation of free formaldehyde. The modified aluminum tripolyphosphate, by virtue of its unique chemical structure, further captures and fixes the residual formaldehyde molecules, thereby achieving a significant reduction in formaldehyde emission.

[0092] In terms of flame retardancy, Examples 1 to 3 also showed excellent strength, and all successfully met the requirements of flame retardancy grade B1-C, where the values ​​of THR600S (total heat release within 600 seconds) were all controlled below 15MJ. This achievement was largely due to the addition of modified aluminum tripolyphosphate. The modified aluminum tripolyphosphate not only enhances the thermal stability of the material, but also forms a protective layer during the combustion process, effectively isolating the transfer of oxygen and heat, thereby significantly improving the flame retardancy of the material.

[0093] (2) Further review of the data in Table 1 shows that there are significant differences between Examples 1 to 3 and the comparative examples in terms of free formaldehyde content, formaldehyde emission and THR600S value. Specifically, the free formaldehyde content and formaldehyde emission of Comparative Example 1 are significantly higher. The reason for this phenomenon is that the three-stage polymerization process was not adopted when synthesizing the urea-formaldehyde resin, resulting in low formaldehyde conversion efficiency, and a large amount of formaldehyde was not effectively converted, so the residual amount was relatively high. At the same time, although modified aluminum tripolyphosphate was also added in the comparative example, due to the excessive residual amount of formaldehyde, its absorption capacity was insufficient and the formaldehyde content could not be effectively reduced.

[0094] Comparative Example 2 is also higher in formaldehyde emission and THR600S value than the examples, mainly because the modified aluminum tripolyphosphate, a key component, is missing in its formula. The modified aluminum tripolyphosphate can not only absorb volatile formaldehyde, but also play a flame retardant role during the combustion process. However, due to the lack of this component in Comparative Example 2, the formaldehyde emission cannot be effectively controlled, and the flame retardant performance is also greatly reduced.

[0095] As for Comparative Example 3, its formaldehyde emission is significantly higher than that of the embodiment, mainly because although aluminum tripolyphosphate is added in this embodiment, it is not modified. Although unmodified aluminum tripolyphosphate also has certain adsorption properties, it cannot effectively solidify the adsorbed formaldehyde in the absence of auxiliary substances such as polyvinyl alcohol and meta-diphenol, so the formaldehyde emission is not significantly improved. This finding once again emphasizes the important role of modified aluminum tripolyphosphate in reducing formaldehyde emission and improving flame retardant properties.

[0096] The above-mentioned implementation modes are preferred implementation modes of a part of the present invention and are not any form of limitation to the present invention. Any other modifications, equivalent changes, modifications and simplifications made to the above implementation modes based on the technical essence of the present invention are within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a modified aluminum tripolyphosphate formaldehyde scavenger, characterized in that: The following steps are involved: Aluminum tripolyphosphate suspension is added to the reactor, and the temperature of the aluminum tripolyphosphate suspension is increased under stirring. The composite modifier is added to the reactor, and after stirring, the modified aluminum tripolyphosphate formaldehyde capture agent is obtained through filter pressing, drying and crushing.

2. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1, characterized in that: The dry basis mass of the aluminum tripolyphosphate suspension is 40-45%.

3. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1, characterized in that: The temperature of the aluminum tripolyphosphate suspension was raised to 65-70°C.

4. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1, characterized in that: The added amount of the composite modifier is 4.5-5% of the aluminum tripolyphosphate dry basis equivalent.

5. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1 or 4, characterized in that: The preparation method of the composite modifier comprises the following steps: adding deionized water into a container, then heating, adding polyvinyl alcohol under stirring conditions, and after the polyvinyl alcohol is completely dissolved, adding ethylene urea and meta-diphenol at the same time, and after both are completely dissolved, cooling the solution to obtain the composite modifier.

6. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1, characterized in that: Add deionized water into the container and heat it to 65-70°C.

7. The method for preparing the modified aluminum tripolyphosphate formaldehyde scavenger according to claim 1, characterized in that: The mass ratio of the deionized water, polyvinyl alcohol, ethylene urea and m-diphenol is (45-50):(10-15):(20-25):(30-35).

8. A process for preparing a highly flame-retardant, environmentally friendly urea-formaldehyde resin adhesive, characterized in that: The following steps are involved: A formaldehyde solution with a content of 35-37% is added to a reaction kettle, and the pH value of the formaldehyde solution is adjusted to between 7.5 and 8.0 using 28-30% sodium hydroxide. Urea is added for the first time in an amount of 80-82% of the total mass of urea, and the stirrer is started, heated to 70-75°C for reaction for 1-2 hours, and the reaction temperature is increased to 80-85°C. Urea is added for the second time in an amount of 13-15% of the total mass of urea, and the reaction is stirred for 1-1.5 hours, and the temperature is increased to 90-95°C. Urea is added for the third time in an amount of 4-6% of the total amount of urea, and the reaction is terminated after 1-1.5 hours. The total mass of the added urea is 1.7-1.8 times the amount of formaldehyde. The modified aluminum tripolyphosphate formaldehyde capture agent described in any one of claims 1 to 7 is added to the reaction kettle, and after being stirred evenly, the material is cooled to room temperature and discharged to obtain a highly flame-retardant and environmentally friendly urea-formaldehyde resin adhesive.

9. A highly flame-retardant, environmentally friendly urea-formaldehyde resin adhesive prepared according to the process of claim 8.

10. An application of the highly flame-retardant, environmentally friendly urea-formaldehyde resin adhesive according to claim 9, characterized in that: Used in the production of artificial boards.

Citation Information

Patent Citations

  • Loss-resistant composite inorganic flame retardant, flame-retardant shaving board applying same and manufacturing method of flame-retardant shaving board

    CN116175715A

  • Method for preparing paper-making black liquor adhesive

    CN101191039A

  • Method for preparing urea-formaldehyde resin adhesive

    CN101191042A

  • Method for preparing urea-formaldehyde resin adhesive

    CN101191043A

  • Preparation method of modified urea-formaldehyde resin

    CN103361014A